Female rats have a different healing phenotype than males after anterior cruciate ligament rupture with no intervention - Morris, Jodie L.; Letson, Hayley L.; Biros, Erik; McEwen, Peter C.; Dobson, Geoffrey P. (Frontiers in Medicine, 2022)
Little is known on the sex-specific healing responses after an anterior cruciate ligament (ACL) rupture. To address this, we compared male and female Sprague-Dawley rats following non-surgical ACL rupture. Hematology, inflammation, joint swelling, range of motion, and pain-sensitivity were analyzed at various times over 31-days. Healing was assessed by histopathology and gene expression changes in the ACL remnant and adjacent joint tissues. In the first few days, males and females showed similar functional responses after rupture, despite contrasting hematology and systemic inflammatory profiles. Sex-specific differences were found in inflammatory, immune and angiogenic potential in the synovial fluid. Histopathology and increased collagen and fibronectin gene expression revealed significant tissue remodeling in both sexes. In the ACL remnant, however, Acta2 gene expression (a-SMA production) was 4-fold higher in males, with no change in females, indicating increased fibroblast-to-myofibroblast transition with higher contractile elements (stiffness) in males. Females had 80% lower Pparg expression, which further suggests reduced cellular differentiation potential in females than males. Sex differences were also apparent in the infrapatellar fat pad and articular cartilage. We conclude females and males showed different patterns of healing post-ACL rupture over 31-days, which may impact timing of reconstruction surgery, and possibly clinical outcome.